2017
DOI: 10.4103/2277-9175.213877
|View full text |Cite
|
Sign up to set email alerts
|

Association of Animal and Plant Proteins Intake with Hypertension in Iranian Adult Population: Isfahan Healthy Heart Program

Abstract: Background:There is evidence regarding the relationship between dietary proteins intake and blood pressure (BP), but they had inconsistent results. Therefore, this study was designed to assess the association between different kinds of protein intake (animal and plant protein) and BP.Materials and Methods:Data were collected from Isfahan Healthy Heart Program. We performed a cross-sectional study among 9660 randomly selected Iranian adults aged ≥19-year-old that they were selected from three large Iranian regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In a cohort study, the intake of total, animal and plant protein were not associated with blood pressure, however, protein from grains showed an inverse association [56]. Results from the Framingham Offspring study demonstrated that both animal and plant protein intakes were associated with reduced risk of elevated blood pressure [57]. A meta-analysis of interventional studies reported an inverse relation between dietary protein intake and blood pressure and no differential effect on blood pressure when animal protein was directly compared to plant protein [58].…”
Section: Discussionmentioning
confidence: 97%
“…In a cohort study, the intake of total, animal and plant protein were not associated with blood pressure, however, protein from grains showed an inverse association [56]. Results from the Framingham Offspring study demonstrated that both animal and plant protein intakes were associated with reduced risk of elevated blood pressure [57]. A meta-analysis of interventional studies reported an inverse relation between dietary protein intake and blood pressure and no differential effect on blood pressure when animal protein was directly compared to plant protein [58].…”
Section: Discussionmentioning
confidence: 97%
“…An interesting scenario was recently offered by He et al [ 40 ], who found a U-shaped relationship between protein consumption and hypertension, with the lowest prevalence of hypertension in individuals with the highest protein intake. Mehrabani et al [ 41 ] proposed an alternative model based on an inverse dose–response association between protein consumption and BP levels. These data might explain why DBP, but not SBP, and continuous, but not categorical data, were significantly associated with protein intake.…”
Section: Discussionmentioning
confidence: 99%
“…Observation-based models have been proposed to explain the possible effects of protein intake on BP levels [ 59 , 60 ]. Accordingly, individuals with HPI are expected to display low BP values, whereas those with moderate-to-low consumption might present normal or even high BP levels [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%